Optimalisasi Facebook Ads Guna Peningkatan Penjualan Batik Pada Pelaku Usaha Batik Christo Surakarta - Indah Handaruwati; Hizkia Yoland (Jurnal Pengabdian Masyarakat STIE Surakarta, 2023)
The pandemic that has occurred in various parts of the world has changed the way transactions and marketing are carried out in various business fields. Batik Christo is a batik manufacturer specifically for men's shirts which have also been affected by the pandemic. The rise of social media as a means of promotion and a new model of transaction during the pandemic has really helped small businesses. Christo's batik was chosen as an object of community service due to complaints of decreased sales during the pandemic. Toko Batik experienced the sluggishness of visitors directly, so it needed a new strategy. The purpose of community service in Christo's batik business is to help find solutions and provide assistance in developing new strategies using social media. The service team provides training and assistance in making Facebook ads and making product photos to advertise on social media. The planned target has been achieved with the existence of a Facebook Page and product catalog displayed on Facebook Adsense.